Alcohol consumption and gastric cancer risk—A pooled analysis within the StoP project consortium. Issue 10 (8th August 2017) - Rota, Matteo; Pelucchi, Claudio; Bertuccio, Paola; Matsuo, Keitaro; Zhang, Zuo‐Feng; Ito, Hidemi; Hu, Jinfu; Johnson, Kenneth C.; Palli, Domenico; Ferraroni, Monica; Yu, Guo‐Pei; Muscat, Joshua; et al.
Abstract : An association between heavy alcohol drinking and gastric cancer risk has been recently reported, but the issue is still open to discussion and quantification. We investigated the role of alcohol drinking on gastric cancer risk in the "Stomach cancer Pooling (StoP) Project, " a consortium of epidemiological studies. A total of 9, 669 cases and 25, 336 controls from 20 studies from Europe, Asia and North America were included. We estimated summary odds‐ratios (ORs) and the corresponding 95% confidence intervals (CIs) by pooling study‐specific ORs using random‐effects meta‐regression models. Compared with abstainers, drinkers of up to 4 drinks/day of alcohol had no increase in gastric cancer risk, while the ORs were 1.26 (95% CI, 1.08–1.48) for heavy (>4 to 6 drinks/day) and 1.48 (95% CI 1.29–1.70) for very heavy (>6 drinks/day) drinkers. The risk for drinkers of >4 drinks/day was higher in never smokers (OR 1.87, 95% CI 1.35–2.58) as compared with current smokers (OR 1.14, 95% CI 0.93–1.40). Somewhat stronger associations emerged with heavy drinking in cardia (OR 1.61, 95% CI 1.11–2.34) than in non‐cardia (OR 1.28, 95% CI 1.13–1.45) gastric cancers, and in intestinal‐type (OR 1.54, 95% CI 1.20–1.97) than in diffuse‐type (OR 1.29, 95% CI 1.05–1.58) cancers. The association was similar in strata of H. pylori infected (OR = 1.52, 95% CI 1.16–2.00) and noninfected subjects (OR = 1.69, 95% CI 0.95–3.01). Our collaborative pooled‐analysis provides definite, more precise quantitative evidence than previously available of an association between heavy alcohol drinking and gastric cancer risk. Abstract : What's new? How strong is the association between alcohol and gastric cancer risk? These authors pooled data from 20 epidemiological studies worldwide to quantify the connection. People who drank up to four alcoholic drinks a day, they found, had similar risk to those who abstained. Those who took more than four drinks per day saw their risk rise by 20%, while those who imbibed most heavily—6 or more drinks per day—boosted their risk by 50%, or for non‐smokers, nearly doubled their risk. Furthermore, they saw the same association with or without H. pylori infection.